Application of seismic refraction tomography for determining ground water potential zone in the Qularaisi area, Sulaimaniyah city, NE Iraq - AMIN, Abdulla K.; AHMED, Kwestan M.; BABAN, Ezzadin N. (Contributions to Geophysics and Geodesy, 2024)
Delineating zones with the potential groundwater contains is a crucial for the effective exploration and extraction of this resource. Six seismic refraction traverses for measuring compressional wave velocities (vp) were conducted in the Qularaisi area, northwest of Sulaimaniyah City in the Kurdistan Region of Iraq to determine the ground water potential zone in the selected area, each traverse has a total length of 230 m, with an inter-geophone spacing of 5 m. The velocities and the thickness of each layer were subsequently calculated based on the obtained data. This analysis provides insights into the geological formation and composition of the area. The interpretation results reveal the presence of three distinct geological layers. The first upper layer consists of clay topsoil deposits characterized by brittle materials, with the thickness ranging from 0 to 4.2 m and seismic velocities (vp) between 339 and 583 m/s. The second layer, with a thickness of 4.2 to 16.8 m and vp values between 1248 and 2650 m/s, corresponds to recent deposits of clay, sand, silt, and gravel, interpreted as unconsolidated sediments. The third layer is characterized as a consolidated marly limestone belonging from the middle Tanjero formation, occurring at depths exceeding 20 metres. This layer reflects a more compact geological structure, distinguishing it from the overlying unconsolidated materials with the vp values ranging from 3606 to 4844 m/s. The seismic refraction results indicate that the aquifer is a sand and gravel inter-granular aquifer at the depth to the saturated groundwater layers in the area ranges from 10 to 25 m whereas lower layer of marl bed reaches to a depth of 40.2 m acts as the impermeable bed.